A Journey into Collaborative Leadership: Moving Toward Innovation and Adaptability. Issue 156 (7th December 2017) - Otter, Ken; Paxton, Doug
Abstract: This case study explores the journey of an executive leadership team seeking to become more collaborative, innovative, and adaptive in their approach to organizational leadership, using a values‐based collaborative leadership program.